The Dynamics of Ambush Marketing Research: A Bibliometric Analysis and Visualisation of Research Trends and Collaborations - George, Joseph; Sebastian, K. S.; Sasikumar, V. Prasobha; K., Salini; Thomas, Sajan N. (International Review of Management and Marketing, 2026)
This study presents a comprehensive bibliometric analysis of ambush marketing research, utilizing data indexed in the Scopus database. Ambush marketing, a tactic employed by brands to gain visibility without official event sponsorship, has emerged as a significant area of inquiry in marketing and sports management. Using Biblioshiny, VOSviewer, and CiteSpace, the analysis maps the intellectual, conceptual, and social structures of the field. The results reveal a consistent growth in scientific output over the years, with notable contributions from researchers such as Burton and Séguin. Prominent journals like the International Journal of Sports Marketing and Sponsorship serve as key dissemination platforms. Country-wise analysis highlights the dominance of research output from the United States, Canada, and Australia. Network visualizations of co-citation and bibliographic coupling indicate strong theoretical foundations and interdisciplinary intersections. Keyword co-occurrence analysis identifies major themes such as guerrilla marketing, sponsorship effectiveness, and consumer response. The thematic map highlights emerging and niche areas requiring further exploration, including legal frameworks and ethical considerations. The study concludes by identifying research gaps and suggesting practical implications for policymakers, sponsors, and marketers to navigate ambush marketing’s evolving landscape.